Forest lights: Notes on the conceptualization of the unconscious - Kohák, Erazim (Journal of religion and health, 1983)
Using the metaphor of lights appearing unexplained in the night, the author argues for a conceptualization of the unconscious based on a posture of trust and acceptance rather than one of fear and explanation.